NON-GOLD FIDUCIARY COLLATERAL VALUE CALCULATION SYSTEM AT PT. PEGADAIAN SYARI'AH UNIT DARUSSALAM BANDA ACEH - Muhammad Maulana; Riska Yulianti (JURISTA: Jurnal Hukum dan Keadilan, 2017)
The amount of financing to be provided by the pawnshop is determined by the value of the collateral submitted by the customer to the management of PT Pegadaian Syari'ah. This study aims to determine how the feasibility assessment of non-gold fiduciary security objects accepted as collateral at PT Pegadaian Syari'ah Darussalam Unit, Banda Aceh? In this research, the author uses a type of qualitative research, this research uses descriptive analysis methods based on library research and field research data. The results of the research found that in calculating the value of non-gold fiduciary collateral at PT Pegadaian Syari'ah Darussalam Unit is guided by the local market price provisions issued regularly by the head office. While the assessment of the feasibility of the non-gold fiduciary guarantee object received as collateral at PT Pegadaian Syari'ah Darussalam Unit is determined by directly seeing the feasibility of the guarantee object by PT Pegadaian Syari'ah to the customer, and also evaluating the real conditions of the feasibility assessment of the object as collateral for Arrum financing. The estimated value of the goods is determined based on the percentage of the price of the goods, which is guided by the Local Market Price and which is sourced in several places such as agents and online sites. Things that affect the value of the object of collateral, namely the object and business, both of which must be balanced, the year of expiration of the motorbike and the physical condition of an object. In the concept of fiqh muamalah, there are no specific provisions regarding the calculation of the value of collateral in this rahn contract. And in some pawn hadiths there is also no clear information obtained, so that the parties can flexibly make their own guarantee value.